SENIOR SERVICES THAT SUPPORT HOUSING FIRST IN METRO VANCOUVER, CANADA. (11th November 2018) - Canham, S; Battersby, L; Lan Fang, M; Wada, M; Barnes, R; Sixsmith, A
Abstract: In order to implement and deliver Housing First, a model and philosophy for housing homeless people in immediate and permanent housing with individualized supports, research is needed on the system of support services as they currently exist. Guided by principles of community-based participatory research, this paper presents findings from a senior-focused deliberative dialogue workshop in Vancouver, Canada. Participants (16 service providers and 1 service recipient) identified services and resources available to support seniors in maintaining housing and barriers and facilitators for accessing services. Data suggest that affordable housing that adapts to changing health conditions, income supports, health services, homecare, transportation, and culturally appropriate and nondiscriminatory informational resources are among the supports needed older adults to succeed under the Housing First model. Barriers to Housing First service provision, including eligibility criteria, should be reconsidered in light of the growing number of older adults who are newly experiencing homelessness.